Individual changes in anthropometric measures after age 60 years: a 15-year longitudinal population-based study. (26th March 2021) - Guo, Jie; Shang, Ying; Fratiglioni, Laura; Johnell, Kristina; Welmer, Anna-Karin; Marseglia, Anna; Xu, Weili
Abstract: Background: weight loss is commonly observed with ageing. We explored the trajectory of body mass index (BMI) and two proxies of muscle mass—calf circumference (CC) and mid-arm circumference (MAC)—and identified their determinants. Methods: within the SNAC-K cohort, 2, 155 dementia-free participants aged ≥60 years were followed over 15 years. BMI, CC and MAC were measured at baseline and follow-ups. Baseline sociodemographic and lifestyle factors were collected through interviews. Diabetes and vascular disorders were diagnosed by physicians through clinical examination and medical records. Data were analysed using linear mixed-effect models stratified by age (younger-old [<78 years] vs. older-old [≥78 years]). Results: over the 15-year follow-up, BMI remained stable among participants aged 60 years at baseline ( β slope = 0.009 [95% confidence interval −0.006 to 0.024], P = 0.234) and declined significantly among those aged ≥66 years, while CC and MAC declined significantly across all age groups. The decline over 15 years in BMI, CC and MAC separately was 0.435 kg/m 2, 1.110 cm and 1.455 cm in the younger-old and was 3.480 kg/m 2, 3.405 cm and 3.390 cm in the older-old. In younger-old adults, higher education was associated with slower declines in all three measures, while vascular disorders and diabetes were associated with faster declines. In older-old adults, vigorous physical activity slowed declines in BMI and CC, while vascular disorders accelerated declines in BMI and MAC. Conclusions: CC and MAC declined earlier and more steeply than BMI. Cardiometabolic disorders accelerated such declines, while higher education and physical activity could counteract those declines.